RETRACTED: Current Developments in Catalytic Methanation of Carbon Dioxide—A Review - Tan, Chung Hong; Nomanbhay, Saifuddin; Shamsuddin, Abd Halim; Park, Young-Kwon; Hernández-Cocoletzi, H.; Show, Pau Loke (Frontiers in Energy Research, 2022)
The utilization of fossil fuel has increased atmospheric carbon dioxide (CO2) concentrations drastically over the last few decades. This leads to global warming and climate change, increasing the occurrence of more severe weather around the world. One promising solution to reduce anthropogenic CO2 emissions is methanation. Many researchers and industries are interested in CO2 methanation as a power-to-gas technology and carbon capture and storage (CCS) system. Producing an energy carrier, methane (CH4), via CO2 methanation and water electrolysis is an exceptionally effective method of capturing energy generated by renewables. To enhance methanation efficiency, numerous researches have been conducted to develop catalysts with high activity, CH4 selectivity, and stability against the reaction heat. Therefore, in this mini-review, the characteristics and recent advances of metal-based catalysts in methanation of CO2 is discussed.